2013
DOI: 10.3349/ymj.2013.54.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of IFN-Gamma and TNF-Alpha Gene Expression and Their Relationship with Disease Progression after Infection withMycobacterium Tuberculosisin Guinea Pigs

Abstract: PurposeGuinea pig is one of the most suitable animal models for Mycobacterium tuberculosis (M. tb) infection since it shows similarities to pulmonary infection in humans. Although guinea pig shows hematogenous spread of M. tb infection into the whole body, immunological studies have mainly focused on granulomatous tissues in lungs and spleens. In order to investigate the time-course of disease pathogenesis and immunological profiles in each infected organ, we performed the following approaches with guinea pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In a study on cytokine gene expression in the M. tuberculosisinfected guinea pig model, the expression of IFN-g was induced at between 3 and 6 weeks of infection and gradually decreased. 29 Such an effect might have influenced the accuracy of test performance, as the duration of infection in the participants enrolled in this study was unclear.…”
Section: Discussionmentioning
confidence: 96%
“…In a study on cytokine gene expression in the M. tuberculosisinfected guinea pig model, the expression of IFN-g was induced at between 3 and 6 weeks of infection and gradually decreased. 29 Such an effect might have influenced the accuracy of test performance, as the duration of infection in the participants enrolled in this study was unclear.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that the close inter-relationship between the coagulation and inflammation may not exist in chronic infections such as TB. Although we cannot rule out the possibility that TF deficiency may have an effect on elaboration of proinflammatory cytokines at the very early stage of the M.tb infection, it is important to note here that expression of inflammatory cytokines in mice and guinea pig following M.tb infection was shown to occur around 2 to 3 weeks post infection, and the expression was persistent for 10 weeks or more [45,46].…”
Section: Discussionmentioning
confidence: 84%
“…Several cytokines, such as TNF-α, TGF-β, and MMP-9, are critical for granuloma formation following Mtb infection ( Iliopoulos et al, 2006 ; Taylor et al, 2006 ; Barry et al, 2009 ; Mootoo et al, 2009 ; Beham et al, 2011 ; Fallahi-Sichani et al, 2011 ; Ramakrishnan, 2012 ; Roh et al, 2013 ; Shmarina et al, 2013 ; Al Shammari et al, 2015 ; Datta et al, 2015 ; Ordonez et al, 2016 ; Warsinske et al, 2017 ; Walton et al, 2018 ). Here, we further characterized the profile of those cytokines in clinical tuberculosis human and Mtb -infected model animal tissues and found that MMP-9 was highly expressed.…”
Section: Discussionmentioning
confidence: 99%